Effects of Increasing Alpha-Linolenic Acid on Growth Performance and Mortality Rate in PRRS-Virus Challenged Nursery Pigs - Jenna J. Bromm; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Josh R. Flohr; Raymond A. M. Schmitt; Jordan T. Gebhardt; Felipe Zarate (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 91,140 weaned pigs, (DNA 600 × PIC 1050; initially 11.33 ± 0.62 lb) originating from PRRSV-positive sow farms, were used across 8 nursery sites to evaluate growth performance, total removal and mortality rate, and medication usage of nursery pigs fed diets containing 0 or 3% O3 Trial Feed (NBO3 Technologies LLC, Manhattan, KS), a source of omega-3 fatty acids. Each of the 8 sites contained 5 barns with 2 rooms in each barn. Rooms of pigs were blocked by nursery site and allocated by sow source to 1 of 2 dietary treatments. Thus, there were 40 groups (rooms) per treatment with approximately 1,100 pigs per room. The first treatment was a standard nursery diet specific to the production system. The second treatment was the same standard nursery diet with the addition of 3% O3 Trial Feed. At placement, pigs were fed a pre-starter and then fed experimental diets across 3 phases with all diets fed in pelleted form. Overall, there were no significant differences (P>0.10) observed in growth performance between pigs fed diets containing 0 or 3% O3 Trial Feed. Pigs fed control diets had reduced (P<0.001) total removals and mortality percentage compared to pigs fed diets containing 3% O3 Trial Feed. When evaluating medication usage, there were no significant differences (P>0.10) observed in the total number of injections given per 1,000 pig days. However, pigs fed diets containing 3% O3 Trial Feed had a reduced (P<0.001) number of total injections per pig placed. In summary, the increase in alpha-linolenic acid in the diet, through the inclusion of 3% O3 Trial Feed, did not impact growth performance during the duration of this trial. There was an increase in total removals and mortality in pigs fed diets containing O3 Trial Feed. However, there was a reduction in total injections given per pig placed in pigs fed diets containing O3 Trial Feed. We hypothesize that because of the high prevalence of PRRS at entry, O3 Trial Feed may not have had sufficient time to impact the immune system before the PRRS challenge.
Keywords: alpha-linoleic acid; omega 3 fatty acids; PRRSv; weanling pigs